Textual Surveillance, Social Codes, and Sublime Voices: The Tyranny of Narrative in Caleb Williams and Wieland - Hogsette, David (Romanticism on the Net, 2005)
AbstractWilliam Godwin and Charles Brockden Brown present narrative and textuality as Gothic mechanisms of psychological terror and political oppression. Godwin's Caleb Williams (1794) directly addresses the issues of social injustice and the abuses of political power that he examines in Enquiry Concerning Political Justice (1793), and these two works had an immense ideological and artistic influence on Brown's American Gothic tale Weiland (1798). Though both authors were in some ways anti-Gothic, they indeed chose this popular genre in order to reach, as Godwin notes in his preface, "persons whom books of philosophy and science are never likely to reach." As the genre dictates, these novels do provide some of the classic Gothic mechanisms such as ruinous dungeons, creepy castles and mansions, and mysterious, dark figures. However, the main source of Gothic terror in these novels is the oppressive misuse of language. Located within the anxiety and uneasiness evoked by these abuses of language and textual entrapments are Godwin's and Brown's political comments concerning the power relationships between governments and individuals.